Comparative Accuracy of Ultrasound and MRI in Diagnosing Rotator Cuff Tears - Dr. Rajkiran Kanhaiya Rathi; Dr. Ketki Ulhas Patil; Dr. Priya Raman Bhole; Dr. Vinod Narayanrao Chaudhari; Dr. Vijay Indal Naik, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Rotator cuff tears are a common cause of shoulder pain and disability, affecting millions of people worldwide. Accurate diagnosis is crucial for effective management and treatment. Ultrasound and MRI are both used for diagnostic imaging of rotator cuff tears, yet their comparative accuracy remains under continuous scrutiny. Objective: To compare the diagnostic accuracy of ultrasound and MRI in the detection of rotator cuff tears. Methods: This retrospective study involved 120 patients who underwent both ultrasound and MRI for suspected rotator cuff tears at a single tertiary care center. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated and compared between the two modalities. Statistical significance was determined using Chi-square and Z-tests where appropriate. Results: MRI demonstrated higher sensitivity (85%) compared to ultrasound (63.33%), with a statistically significant difference (p=0.001). Although both modalities showed high specificity—MRI at 95% and ultrasound at 87.5%—the difference was not statistically significant (p=0.064). MRI also exhibited a higher PPV (92.73%) compared to ultrasound (84.44%) with statistical significance (p=0.023). The NPV and overall accuracy were similarly high for both modalities but did not show significant differences. Conclusion: MRI is superior to ultrasound in terms of sensitivity and positive predictive value in diagnosing rotator cuff tears. Although both imaging modalities provide high specificity and accuracy, MRI should be considered the more reliable method for confirming rotator cuff pathology, especially in complex cases. Nevertheless, ultrasound remains a valuable tool for initial assessments given its cost-effectiveness and real-time imaging capabilities.